LAMA PERENDAMAN TUMPATAN SEMENTARA BAHAN CAVIT DAN FLETCHER DALAM SALIVA BUATAN TERHADAP KEKUATAN TEKAN - Hariyanto Hariyanto; Susilarti Susilarti; Dwi Suyatmi (Journal of Oral Health Care, 2015)
Background: The appropriate temporary fillings may becomean important factor to determines the success orfailure of dental care. Temporaryfillingmaterialscould beusefultoprevent theingress of liquids, microorganismsandotherimpuritiesintocavity. It could alsopreventedthe release ofdrugswhich are placedinthe pulpchamberandroot canalsystem. Compressive strength isan important trait in the fillings, especially in the process ofmastication. If the received load is bigger than the strengthof fillings then the fillings will be broken. The damaged orbroken fillings ahead of time can interfere with patientsand hamper the objectives to be achieved.Objective: To determine the effect long time soaking of thetemporary filling material Cavit and fletcher in artificial salivafor compressive strength.Methods: The experimental laboratories research withquota technique sampling, totaling 24 samples. The researchwas conducted from August to September 2013 inthe Faculty of Materials Laboratory Department of Mechanicaland Industrial Engineering Gajah Mada University. Thecylindrical samples (discs) with a height of 6 mm and adiameter of 4 mm is stored in an incubator at 37°C. Temporaryfilling materials of cavit and fletcher compressivestrength were measured by Universal Testing Machine toolafter soaking for 1 hour, 1 day, 3 days and 7 days in artificialsaliva.Results: Significance values of 0.001 and 0.027 (p < 0.05),so there is the effect long time soaking of the temporaryfilling material Cavit and fletcher in artificial saliva for compressivestrength.Conclusion: The longer soaking of the temporary fillingmaterial Cavit in artificial saliva compressive strength gettingbetter, the maximum compressive strength in soakingfor 3 days, after 3 days of compressive strength decreased.The longer soaking of the temporary filling material Fletcherin artificial saliva compressive strength decreased, themaximum compressive strength in soaking for 1 hour.The compressive strength of materials Cavit is better thanFletcher.